Complement resistance impairs anti-tumour therapy - Konatschnig, Thomas (Radiology and oncology (Ljubljana), 2006)
Background. Various studies during the last two decades clearly indicate that resistance of human tumour cells to autologous complement is mainly based on the expression of membrane-bound complement regulatory proteins (mCRP) like CD59, CD55 and CD46 with good evidence for a predominant role of CD59. Beyond these in vitro findings the importance of this phenomenon for the patients outcome now becomes evident from first clinical studies. Overcoming complementresistance of tumour cells is therefore considered a promising way to improve therapeutic options and prognosis in a variety of cancer diseases. In this short review two feasible approaches are discussed in more detail: (1)neutralisation of mCRP by monoclonal or recombinant antibodies and (2) genesilencing strategies to down-regulate mCRP by blocking the expression of these proteins on the RNA level using siRNA. Conclusions. As mCRP are also present on all normal tissues like endothelial cells, parenchymatous organs (liver, kidney etc.) or blood cells, mCRP blocking strategies have to be targeted selectively to malignant cells sparing the surrounding healthy tissues from the deleterious complement attack. Despite first encouraging results, translation of mCRP inhibition to improve antibody-based immunotherapy into the clinic is still a great challenge.
Keywords: Antibodies, Monoclonal; antigeni; Antigeni, CD59; Antigens, Cd59; Complement Inactivators; Drug Therapy; Immunology; Immunotherapy; Imunoterapija; Komplement, inaktivatorji; Neoplasms; Novotvorbe; odpornost; onkologija; Protitelesa monoklonska; tumor; tumorske celice